EVALUASI DAN DESAIN SSU KARYAWAN UKM XYZ DI KABUPATEN BOGOR MENGGUNAKAN METODE POINT SYSTEM - Respati Mandalagiri; Naila Zahra; Salsa Lubnaa Dewi; Zaidan Muafy Althaf (Jurnal Pijar, 2026)
The unstructured compensation system at SME XYZ causes discrepancies between job values and employee salaries, marked by red circle rates and low inter-grade spreads, necessitating evaluation for proportionality. This study aims to evaluate and redesign the salary structure for SME XYZ employees in Ciomas, Bogor Regency. Employing a descriptive quantitative approach, the population and sample comprise all salary data from 28 employees. Primary data were collected through interviews, job analysis questionnaires, salary surveys, and secondary data from literature reviews, conducted February–March 2025. Data analysis includes pre-improvement salary mapping, determination of 10 compensable factors based on Hay Group (2005) and Committee (2009), job value assessment using Hay System, given grade job grading method, and salary structure design with adhered point system. Findings reveal the initial salary structure was disproportionate to job values; redesign produces 4 grades (job value 402-755) with salary ranges Rp2,200,000–Rp5,082,000 and total salary increase of Rp49,899,200. Implications support equitable compensation to enhance employee motivation and retention in SME.​